THE ROLE OF CONNECTIVE TISSUE DYSPLASIA IN UTERINE SCAR INSUFFICIENCY AFTER CESAREAN SECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This review explores the key role of connective tissue dysplasia in the development of uterine scar defects after cesarean section. Abnormal collagen synthesis and extracellular matrix disruption impair wound healing, increasing the risk of scar dehiscence and rupture, especially in patients with hereditary connective tissue disorders. Molecular factors such as imbalanced collagen types and altered enzyme activity contribute to poor tissue repair. Improved diagnostics using biomarkers, imaging, and genetic screening help identify high-risk individuals. Current management highlights multidisciplinary care, preconception counseling, and personalized delivery planning. This synthesis supports better clinical decisions and improved outcomes.